2012
DOI: 10.1183/09031936.00120012
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disordered breathing in patients receiving therapy with buprenorphine/naloxone

Abstract: Patients using chronic opioids are at risk for exceptionally complex and potentially lethal disorders of breathing during sleep, including central and obstructive apnoeas, hypopnoeas, ataxic breathing and nonapnoeic hypoxaemia. Buprenorphine, a partial m-opioid agonist with limited respiratory toxicity, is widely used for the treatment of opioid dependency and chronic nonmalignant pain. However, its potential for causing sleep disordered breathing has not been studied.70 consecutive patients admitted for thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 34 publications
1
39
1
Order By: Relevance
“…Conversely, to our knowledge there is a lack of studies systematically addressing this issue, and previous studies have found no relationship between multiple drug usage and chronic opioid-associated central sleep apnea. 31,39,40 Secondly, we took into account both pauses in respiratory signal and scored sleep apneas to characterize respiratory variability. These events, which tend to have longer durations than normal breaths, would create spikes in the inter-breath interval signal.…”
Section: Limitationsmentioning
confidence: 99%
“…Conversely, to our knowledge there is a lack of studies systematically addressing this issue, and previous studies have found no relationship between multiple drug usage and chronic opioid-associated central sleep apnea. 31,39,40 Secondly, we took into account both pauses in respiratory signal and scored sleep apneas to characterize respiratory variability. These events, which tend to have longer durations than normal breaths, would create spikes in the inter-breath interval signal.…”
Section: Limitationsmentioning
confidence: 99%
“…These events include central and obstructive apneas, and hypoventilation. 2,4,5 We report the case of a patient who underwent multiple sleep studies on and off opioids and with and without continuous positive airway pressure (CPAP) therapy. These studies strongly indicate that opioids were the cause of her central sleep apnea (CSA), and also emergent CSA with commencement of CPAP and bilevel positive airway pressure (PAP) therapy.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] One study found that 75% of patients on chronic opioid therapy had an AHI ≥ 5 events per hour and 36% had severe sleep apnea (AHI ≥ 30 events/h). 4 Another study found that 70% of patients on chronic opioid therapy had evidence of ataxic breathing.…”
Section: Discussionmentioning
confidence: 99%